KEJAHATAN-KEJAHATAN PERANG DALAM HUKUM INTERNASIONAL - Antonius Janga (Litbang STFT Widya Sasana Malang, 2002)
This article deals philosophically with the war crimes against humanity in the international law. The study focuses on the understanding of what we mean by the war crime and its historical development. The war crimes presuppose the list of the unlawful materials or cruel actions by which we mean violation against humanity. The author offers analysis of war crimes from the perspective of the international law or international convention concerning war. He suggests that the knowledge of what may be called “war crimes” is indispensable, as our time is at war (actually war on Iraq by the Allies). In addition, in a war-time the law enforcement seems to be in vain as well. The author tries to impose the indisputable human treatment toward those who are involved in war. The people should be respected humanly regardless of war-time.